A brackish diatom, Pseudofrustulia lancea gen. et sp. nov. (Bacillariophyceae), from the Pacific coast of Oregon (USA) - Sawai, Yuki; Nagumo, Tamotsu; Nelson, Alan R. (Phytotaxa, 2016)
Light and electron microscope observations show that a brackish diatom taxon should be classified as a new species of a new genus; Pseudofrustulia lancea gen. et sp. nov. We propose separating Pseudofrustulia from other similar genera such as Frickea, Frustulia, Amphipleura, Muelleria, and Envekadea on the basis of its thickened axial ribs, raphe endings, axial costae, morphology of helictoglossa, size of striae on valve surfaces, and areolae on the inner side between its axial ribs and raphe. Girdle bands may be another diagnostic feature for the separation of Pseudofrustulia from related taxa, but more detailed observations using SEM images are required to determine if bands are diagnostic.